Microfuel Inventory And Its Potential As Biofertilizer And Agensia Biological Controller On The Land Of Coal Mine Reclamation In Samarinda - Rosfiansyah, Sopialena, Surya Sila . (Universitas 17 Agustus 1945 Samarinda, 2017)
The fungus in the soil naturally has a role to maintain soil function, to control its productivity and play a role in the biological control of plant-disturbing organisms. This study aims to determine the diversity of micro fungi as well as their potential as biofertilizer and biological control agents in the reclamation field of coal mines in Samarinda. This research is a descriptive research. The research was conducted in the reclamation field of coal mine of PT. CEM (Cahaya Energi Mandiri) Tanah Datar Samarinda. The research results show that there are 6 genus on 9 month reclamation field ie Fusarium, Massarina, Humicola, Rhizoctonia, Blastomyces, and Pythium. 15 genus of fungi on the 24-month reclamation field ie Mortierella, Humicola, Penicillium, Pythium, Aspergillus, Trichoderma, Blastomyces, Fusarium, Anixiella Verticillium, Gliocladium, Entomophaga, Metarhizium, Mucor, Chloridium. All genera have a role in the soil biofertilizer process, except for the unknown genus Anixiella. There are 3 genera that have the role as an insect pathogen that can be utilized in plant pest control Fusarium, Entomophaga and Metarhizium. There are 2 genera that have antagonistic role in biological control of plant disease pathogen namely Gliocladium and Trichoderma.